The genus Euurobracon Ashmead (Hymenoptera, Braconidae, Braconinae) in China, with description of three new species - Li, Yang; He, Jun-Hua; Chen, Xue-Xin (Zootaxa, 2016)
The species of the genus Euurobracon Ashmead (Hymenoptera, Braconidae, Braconinae) from China are revised and six species are recognized, including three new species (E. acuminatus sp. nov., E. disparalis sp. nov., and E. unicolor sp. nov.), which are described and illustrated. Also, E. triplagiata (Cameron, 1900), is reported from China for the first time. A key to the Chinese species of this genus is provided.